Reduction of electric energy consumption for heating passenger railway carriages - A. А. Kuznetsov; S. S. Gorobei (Омский научный вестник)
The article provides an overview of circuit solutions and describes the elements of power supply system of a passenger car. A combined heating system for a passenger car is described. The results of experimental studies on saving electrical energy using voltage regulators are presented. The article proposes an algorithm for controlling electric heaters based on the use of semiconductor power regulators. Experimental studies using the proposed high-voltage regulators as part of passenger car heaters made it possible to reduce the cost of power supply for a passenger car from 3 % to 5 % during their operation.